2010
DOI: 10.1359/jbmr.091006
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover markers and prediction of fracture: A prospective follow-up study of 1040 elderly women for a mean of 9 years

Abstract: Osteoporosis is characterized by compromised bone mass and strength, predisposing to an increased risk of fracture. Increased bone metabolism has been suggested to be a risk factor for fracture. The aim of this study was to evaluate whether baseline bone turnover markers are associated with long-term incidence of fracture in a population-based sample of 1040 women who were 75 years old (Malmö OPRA study). Seven bone markers (S-TRACP5b, S-CTX-I, S-OC[1-49], S-TotalOC, S-cOC, S-boneALP, and urinary osteocalcin) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 30 publications
6
94
1
2
Order By: Relevance
“…Furthermore, our observations of BTMs in relation to the prediction of ORFs are consistent with the recent study of Ivaska and colleagues, (26) who demonstrated that only BRMs (namely serum tartrate-resistant acid phosphatase active isoform 5b [s-TRACP-5b], s-CTx, and urinary OC) were associated with increased fracture risk for up to a decade in elderly women with no association of BFMs with fracture prediction.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our observations of BTMs in relation to the prediction of ORFs are consistent with the recent study of Ivaska and colleagues, (26) who demonstrated that only BRMs (namely serum tartrate-resistant acid phosphatase active isoform 5b [s-TRACP-5b], s-CTx, and urinary OC) were associated with increased fracture risk for up to a decade in elderly women with no association of BFMs with fracture prediction.…”
Section: Discussionsupporting
confidence: 92%
“…36 There are modest but significant associations of BTM with fracture in women and men. [43][44][45][46] Still, there have been uncertainties over the use of BTM in routine clinical practice to assess fracture risk because of inter-and intra-individual variability. 47,48 Although a recent study suggested that BTM also reflect cortical bone architecture in addition to fracture risk, 31 further studies are needed to evaluate the independent role of BTM in fracture risk prediction.…”
Section: Bone Turnover Markers Cortical Porosity and Fracturementioning
confidence: 99%
“…Incident fractures during the follow--up period (until November 2006) were recorded and verified by review of the related medical records [17]. In this report, clinical symptomatic vertebral fractures from age 50 upwards were analysed.…”
Section: Dxa Measurement Visual Assessment Of Spine Degenerative Manmentioning
confidence: 99%